Chapter Un manifesto per la modernità: venti anni di Utopia e disincanto - Carciaghi, Federico (Biblioteca di Studi di Filologia Moderna, 2021)
The current essay aims to highlighting the importance of Magris' Utopia e disincanto. The year of its first publication (1999) was a watershed moment in his career, as it paved the way to a new season of public engagement and historical analysis, which can be also seen in his later essays and novels. Twenty years later, Utopia e disincanto is still a manifesto for modernity, a deeply contemporary book where Magris' analytical view is headed towards an idea of universal literature, an idea of Weltliteratur that should be a tool to understand the changes in which mankind is involved. Literature is meant to be a tool to investigate the dark sides hidden among the folds of History